2021
DOI: 10.34133/2021/9895241
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Seasonal and Circadian Rhythms in Structural Traits of Field Maize from LiDAR Time Series

Abstract: Plant growth rhythm in structural traits is important for better understanding plant response to the ever-changing environment. Terrestrial laser scanning (TLS) is a well-suited tool to study structural rhythm under field conditions. Recent studies have used TLS to describe the structural rhythm of trees, but no consistent patterns have been drawn. Meanwhile, whether TLS can capture structural rhythm in crops is unclear. Here, we aim to explore the seasonal and circadian rhythms in maize structural traits at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
0
14
0
1
Order By: Relevance
“…Thanks to the development of active sensors (e.g. LiDAR; Guo et al., 2018b ) and high-throughput phenotyping facilities (e.g., gantries; Guo et al., 2016 ), diurnal plant phenotyping (e.g., circadian rhythms; Chaudhury et al., 2019 ; Jin et al., 2021a ) can be fully achieved, enabling higher temporal analysis of plant growth.…”
Section: How To Link Prs To G × P × E Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the development of active sensors (e.g. LiDAR; Guo et al., 2018b ) and high-throughput phenotyping facilities (e.g., gantries; Guo et al., 2016 ), diurnal plant phenotyping (e.g., circadian rhythms; Chaudhury et al., 2019 ; Jin et al., 2021a ) can be fully achieved, enabling higher temporal analysis of plant growth.…”
Section: How To Link Prs To G × P × E Studiesmentioning
confidence: 99%
“…LiDAR, as an active sensing technology, is less affected by environmental light conditions and has been successfully used to explore the seasonal and circadian rhythms of plant growth at the individual and organ levels ( Puttonen et al. 2016 , 2019 ; Herrero-Huerta et al., 2018 ; Jin et al., 2021a ). However, in situ measurements occur only at a specific time and place, and the resulting conclusions may not be universal.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…This measurement method is substantially affected by the subjective factors of experimenters and is prone to errors. To address this problem, recent studies used a laser scanner and performed image-based fixed-point plant height extraction and RGB-D camera plant height measurement [ 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still the most widely adopted way due to its visibility and reliability during the past decades. Recently, many studies have demonstrated CH can be efficiently acquired from advanced three-dimensional (3D) sensing techniques [ 28 , 30 , 43 , 59 , 68 ]. It brings us naturally to a fundamental and essential question: are 3D sensing techniques as accurate as field measurement?…”
Section: Introductionmentioning
confidence: 99%